Invisibility in global health: a case for disturbing bioethical frameworks - Alenichev, A; Suwalowska, H; Faure, MC; Ng, SH; Modlin, C; Ambrogi, I; Parker, M; Kingori, P (F1000Research, 2023)
In recent years, the global health community has been increasingly reporting the problem of ‘invisibility’ as aspects of health and wellbeing that are often overlooked and ignored, and predominantly affects the most marginalized and precarious people. However, it is unclear how to realistically manage global health invisibility and move forward. In this letter, we reflect on several case studies of invisibility experienced by people in Brazil, Malaysia, West Africa and other transnational contexts. Highlighting the complex nature of invisibility and its interconnectedness with social, political and economic issues and trends, we argue that while local and targeted interventions might provide relief and comfort locally, they will not be able to solve the underlying causes of invisibility. Moving forward, we argue that in dealing with an intersectional issue such as invisibility, twenty-first century global health bioethics could pursue a more ‘disturbing’ framework, challenging the narrow comforting solutions and sociomaterial inequalities of the sociopolitical status quo. We highlight that comforting and disturbing bioethical frameworks should not be considered as opposing sides, but as two approaches working in tandem in order to achieve the internationally set global health milestones of providing better health and wellbeing for everyone. In doing so, we call for taking seriously insights from sociology, anthropology, postcolonial studies, history, feminist studies and other styles of critical reasoning that have long been disturbing the grand assumptions about people and their conditions, and, practically, to rediscover the ethos of the WHO Alma Ata Declaration, calling for cooperation and support beyond the narrow market logic that dominates the landscape of contemporary global health.